Price of political will : the fall of two regimes - Desker, Barry (2021)
Echoes of the fall of Saigon and Phnom Penh in the 1970s, Southeast Asian governments had to contend with upheavals not dissimilar to what Afghanistan’s neighbours are experiencing now. In both instances, the absence of political will proved as painful as it was pivotal.